2018
DOI: 10.1084/jem.20170928
|View full text |Cite
|
Sign up to set email alerts
|

Guidance of super-enhancers in regulation of IL-9 induction and airway inflammation

Abstract: Xiao et al. demonstrate that formation of super-enhancers at Il9 locus is critical for robust IL-9 expression and Th9 cell induction, and assembly of Il9 super-enhancers is driven by OX40-mediated chromatin acetylation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 38 publications
3
48
0
Order By: Relevance
“…In allergic lung inflammation, Xiao et al (19) found that the acetylation of histones (specifically, H3K27) mediates IL-9 expression. Lloyd and Harker (18) also reported that acetylation of histones mediates IL-9 in asthma, and inhibition of H3K27 acetylation decreases the expression of IL-9.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In allergic lung inflammation, Xiao et al (19) found that the acetylation of histones (specifically, H3K27) mediates IL-9 expression. Lloyd and Harker (18) also reported that acetylation of histones mediates IL-9 in asthma, and inhibition of H3K27 acetylation decreases the expression of IL-9.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of H3K27 acetylation could decrease the expression of IL-9. Xiao et al (19) also found that acetylation of histones (specifically, H3K27) promoted transcription of IL-9. H3K27 is a specific histone protein (H3) that is acetylated at lysine 27 (H3K27Ac), a marker of transcriptional activity.…”
Section: Introductionmentioning
confidence: 96%
“…Unlike other costimulatory molecules, OX40 is not expressed by resting naive T cells, but its expression is rapidly induced upon T cell activation, and OX40 costimulation plays a critical role in cell survival, proliferation, and generation of memory cells (Croft, 2010). We and others have shown that OX40 regulates the induction of multiple T helper (T H ) cell subsets, primarily through triggering chromatin modifications that control accessibility of key transcription factors to target loci (Xiao et al, 2016, 2018). In certain models, OX40 strongly promotes the induction of T H 1, T H 2, and T H 9 cells, whereas in other conditions, it inhibits the generation of T H 17 cells and Foxp3 + Tregs (Ito et al, 2005; Li et al, 2008; Vu et al, 2007; Xiao et al, 2012a).…”
Section: Introductionmentioning
confidence: 99%
“…In a different model, we showed that RelB is capable of recruiting the histone acetyltransferase p300/CBP to the Il9 locus to catalyze H3K27 acetylation (an active chromatin mark), consequently mediating robust Th9 induction. 59 However, the factors determining the selectivity of RelB in engaging functionally different chromatin modifiers, separate from its classic role as a transcription factor, remain unknown and warrant further investigation.…”
Section: Nf-κb Family Members As Chromatin Modifiersmentioning
confidence: 99%
“…In a mouse model of allergic lung inflammation, we showed that the challenge of ovalbumin-sensitized mice induces extensive airway inflammation, especially when the OX40 receptor is concurrently stimulated. 59 Further in vitro studies showed that OX40 signaling is exceptionally potent in driving the differentiation of Th9 cells, which are responsible for epithelial hyperplasia, mucin production, and mast cell accumulation in the airways. Interestingly, the induction of Th9 cells by OX40 receptor stimulation is mediated primarily by the formation of superenhancers at the Il9 locus.…”
Section: Chromatin Modifier-targeted Interventions As Potential Theramentioning
confidence: 99%